Cation-mediated, substituent-controlled, C-2-C-7 cycloaromatization of an enyne-allene - Saalfrank, Rolf W.; Haubner, Martin; Deutscher, Christian; Bauer, Walter; Clark, Timothy (Journal of Organic Chemistry, 1999)
Reaction of(2-bromophenylethynyl)trimethylsilane 1 with trimethyl berate yielded the alkynearyl-boronic acid 2, which was coupled in situ with the bromoallenes 3 to give enyne-allenes 4. The intermediates 4 underwent a spontaneous cation-mediated C-2-C-7 cycloaromatization with a concomitant 1,2-shift of the trimethylsilyl group to give the naphthalene derivatives 5. Besides 5, yne-allenes 10 were isolated by chromatography of the crude reaction products. A key step in the formation of 10 is the hydrolysis of the aryl boronic acid 2, which led to phenylethynyltrimethylsilane 8. Under the reaction conditions used, the TMS group of 8 was subsequently removed to give phenylacetylene 9, which further reacted with the bromoallenes 3 to furnish the yne-allenes 10.